Pemberdayaan Masyarakat dalam Upaya Meningkatkan Kepemilikan Kartu Identitas Anak di Taman Kanak-Kanak Daerah Pedesaan: Community Empowerment in Efforts to Increase Child Identity Card Ownership in Kindergartens in Rural Areas - Nikmatur Rohmah; Siti Kholifah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
A Child Identity Card (CIC) is a card issued by the Government to collect data and provide child protection. However, not all preschoolers have CIC. This service aims to provide CIC ownership solutions in rural areas. The service method is applying science and technology and community empowerment. Empowerment is carried out by kindergarten teachers and the surrounding community. The facts at the service location show that 30 children do not have CIC. Thirty-three percent of children who do not have CIC do not have a birth certificate. As many as 57.1% of parents of children who do not have birth certificates do not register their marriage at the Office of Religious Affairs. Parents do not have time to take care of CIC. Parents feel CIC is not necessary. The online CIC program has difficulties; parents do not have cellphones, cellphones are not active, and they cannot create emails. The result of the empowerment is that teachers are skilled in proposing birth certificates and CIC offline and online through the Jember Regency Dispendukcapil Service Information System application. The result of the service is that 24 preschool children have KIA, and five children have birth certificates. Teacher participation should be optimized to increase the ownership of CIC for preschool children.